2020
DOI: 10.1080/16878507.2020.1743480
|View full text |Cite
|
Sign up to set email alerts
|

Modification of bacterial cell membrane to accelerate decolorization of textile wastewater effluent using microbial fuel cells: role of gamma radiation

Abstract: The aim of the present work was to increase bacterial adhesion on anode via inducing membrane modifications to enhance textile wastewater treatment in Microbial Fuel Cell (MFC). Real textile wastewater was used in mediator-less MFCs for bacterial enrichment. The enriched bacteria were pre-treated by exposure to 1 KGy gamma radiation and were tested in MFC setup. Bacterial cell membrane permeability and cell membrane charges were measured using noninvasive dielectric spectroscopy measurements. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Screening of biosurfactant production using different S. marcescens strains was performed as an initial step. S. marcescens N2 with the highest production was identified as prodigiosin hyper producing strain in a previous study [ 16 ]. Variation between S. marcescens isolates could be intrinsic within every strain capable of biosurfactant production.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of biosurfactant production using different S. marcescens strains was performed as an initial step. S. marcescens N2 with the highest production was identified as prodigiosin hyper producing strain in a previous study [ 16 ]. Variation between S. marcescens isolates could be intrinsic within every strain capable of biosurfactant production.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, 1000 Gy was enough to induce permeability of Bacillus sp. producing biosurfactant (Selim et al, 2020) their results showed that this dose is enough to induce changes without compromising the bacterial viability. The obtained results con rm that low dose gamma radiation can be used for enhancing biorecovery without affecting biosurfactant structure and characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…From this stand point; gamma radiation can be considered an effective tool for release of biosurfactant from bacterial cells. Gamma radiation was previously used to permeabilize the cell wall of gram positive bacteria to help release biomolecules to the media (Selim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%